Structural polymorphism of the low-complexity C-terminal domain of TDP-43 amyloid aggregates revealed by solid-state NMR - Shenoy, Jayakrishna; Lends, Alons; Berbon, Mélanie; Bilal, Muhammed; El Mammeri, Nadia; Bertoni, Mathilde; Saad, Ahmad; Morvan, Estelle; Grélard, Axelle; Lecomte, Sophie; Theillet, François-Xavier; Buell, Alexander K.; et al. (Frontiers in Molecular Biosciences, 2023)
Aberrant aggregation of the transactive response DNA-binding protein (TDP-43) is associated with several lethal neurodegenerative diseases, including amyotrophic lateral sclerosis and frontotemporal dementia. Cytoplasmic neuronal inclusions of TDP-43 are enriched in various fragments of the low-complexity C-terminal domain and are associated with different neurotoxicity. Here we dissect the structural basis of TDP-43 polymorphism using magic-angle spinning solid-state NMR spectroscopy in combination with electron microscopy and Fourier-transform infrared spectroscopy. We demonstrate that various low-complexity C-terminal fragments, namely TDP-13(300-414), TDP-11(300-399), and TDP-10(314-414), adopt distinct polymorphic structures in their amyloid fibrillar state. Our work demonstrates that the removal of less than 10% of the low-complexity sequence at N- and C-termini generates amyloid fibrils with comparable macroscopic features but different local structural arrangement. It highlights that the assembly mechanism of TDP-43, in addition to the aggregation of the hydrophobic region, is also driven by complex interactions involving low-complexity aggregation-prone segments that are a potential source of structural polymorphism.